BARRIERS TO THE IMPLEMENTATION OF THE NATIONAL POLICY FOR COMPREHENSIVE MEN’S HEALTH CARE: UPDATED PERSPECTIVES ON MASCULINITIES, TECHNOLOGIES, AND EPIDEMIOLOGICAL CHALLENGES - Fernando do Nascimento, Luis (Health and Society, 2025)
The National Policy for Comprehensive Men’s Health Care (PNAISH), implemented in 2009, represents an important milestone in Brazilian public health. However, more than a decade after its launch, significant barriers persist that compromise its effectiveness. This article presents an integrative literature review that analyzes the sociocultural, institutional, and epidemiological factors that hinder the implementation of PNAISH, incorporating updated perspectives on masculinities, technological innovations, and epidemiological data from the period 2023-2025. The research identified that hegemonic masculinity continues to be a central obstacle, now understood in light of concepts such as toxic masculinity and its implications for mental health. Additionally, it was observed that emerging technologies such as telemedicine and artificial intelligence have significant potential to transform access to men’s health, although their implementation is still limited. It is concluded that the effective implementation of the National Policy for Comprehensive Men’s Health (PNAISH) requires a multifaceted approach that integrates the deconstruction of gender stereotypes, the strengthening of primary care, the incorporation of technological innovations, and an intersectional perspective.